Dialog Keagamaan Menurut Tarmizi Taher Dan Relevansinya Terhadap Pemberdayaan Umat - Mawardi Mawardi (Kamaya: Jurnal Ilmu Agama, 2021)
Indonesia is a country that has various ethnicities and religions which are a multicultural wealth. The next problem is that inter-religious conflicts are prone to occur if religious differences are not regulated and controlled properly. Differences in point of view between each religion will cause religious problems that have an impact on religious tolerance. Therefore, according to Tarmizi Taher, it is necessary to carry out religious dialogue so that fellow believers understand each other. If each religion does not find common ground for their beliefs, at least they can respect each other's differences. According to Tarmizi Taher, dialogue is closely related to the empowerment of the people. Dialogue without further empowerment will be temporary (temporal), therefore it is necessary to empower the people as a further step in maintaining religious harmony. Religious dialogue is ideal when it is displayed between fellow religious leaders. Furthermore, each leader will provide an understanding to each congregation regarding the importance of tolerance in order to live. The empowerment of Tarmizi Taher people includes economic empowerment, poverty eradication, empowerment of religious teachings, ethical empowerment and social empowerment.